Molecular Weight Dependence of Exciton Diffusion in Poly(3‐hexylthiophene). Issue 11 (6th August 2013) - Masri, Zarifi; Ruseckas, Arvydas; Emelianova, Evguenia V.; Wang, Linjun; Bansal, Ashu K.; Matheson, Andrew; Lemke, Henrik T.; Nielsen, Martin M.; Nguyen, Ha; Coulembier, Olivier; Dubois, Philippe; Beljonne, David; et al.
Abstract A joint experimental and theoretical study of singlet exciton diffusion in spin‐coated poly(3‐hexylthiophene) (P3HT) films and its dependence on molecular weight is presented. The results show that exciton diffusion is fast along the co‐facial π–π aggregates of polymer chromophores and about 100 times slower in the lateral direction between aggregates. Exciton hopping between aggregates is found to show a subtle dependence on interchain coupling, aggregate size, and Boltzmann statistics. Additionally, a clear correlation is observed between the effective exciton diffusion coefficient, the degree of aggregation of chromophores, and exciton delocalization along the polymer chain, which suggests that exciton diffusion length can be enhanced by tailored synthesis and processing conditions.